PSYCHOSOCIAL PROBLEMS FOR FORMER COMBATANTS AND VETERANS OF THE HOMELAND OF ANGOLA - Mendes, Cirilo Armando António (2023)
In the existentialist conception, psychosocial suffering is a condition of human existence, just like joy and love. Suffering is a feeling that we go through in some moments of our life, and what we have to do is to perceive and deal with it, instead of trying to avoid it. However, the psychological aspects of the problem are the "manifestation of human subjectivity in the face of the disease, such as feelings, desires, speech, thoughts and behaviors, fantasies and memories, beliefs, dreams, conflicts, lifestyle and the style of getting sick. Objective: to know the psychosocial suffering of former combatants and veterans of the homeland. Methodology: This is a descriptive, exploratory study. For data collection, the technique was used as an interview and the Holmes and Rahe Social Readjustment Scale was applied as an instrument.  The study sampling was census for both models (Quan-qual). The study was conducted in the Municipality of Malanje, Angola. Former combatants and veterans of the homeland with psychosocial problems of both sexes, aged between 50 and 85 years, were included. As for the exclusion criteria, former combatants and veterans of the homeland without psychosocial problems did not include. Findings: Regarding the levels of psychosocial problems, moderate to worrying prevailed for both sexes and marital status. It should be noted that all participants presented some level of psychosocial problem.